Electronic media and social issues in Algeria The podcast technique is a model - Boujfgouf, AL-Zahra (ALBAHITH ALALAMI, 2018)
This study we have made a subject of fanny podcast in electronic media, as a new way to express different issues by the public, This study focuses started on how to address social issues in Alegria by ANAS TINA vidéo on the youtube network , you are to know the trends of young amateur about the various issues dealt with as well as the most important methods used to convince browsers. The researcher used the survey method based on studying 10 episodes videos of blogger ANAS TINA. The result of the study found that the most important issues are the abduction of children, teaching in Algeria; women in Algeria, The negative aspects of the issues addressed have been established in order to direct public opinion and awareness of phenomena prevalent in society.